Bases teóricas para la implementación del concreto autorreparable en laboratorios de enseñanza superior (2021)
Concrete is one of the most widely used materials for the structuring of different buildings such as homes, schools, shopping centers, bridges, and the road network of the different cities and municipalities. This implies a large consumption of this cementitious material, in the case of Colombia for the period established between July 2020 and June 2021, there have been produced 13,454.9 thousand tons of gray cement (DANE, 2021). This material is characterized by its resistance and durability; however, microcracks may exist in the matrix of cement as a result of mechanical load and environmental load; Due to their small size they are not visible and give way to the formation of larger cracks due to the pore connectivity. These larger cracks provide a path for aggressive substances that cause corrosion, which accelerates the deterioration of the structural properties of the material and is a serious threat to the safety, integrity and durability of concrete (Gonzalez et al., 2018; Li, 2018). On the other hand, the production of Cement for different types of material generates carbon dioxide (CO2) emissions. For every 1000 g of cement, approximately 900 g of CO2 are produced (ENNOMOTIVE, 2020), This compound is part of the greenhouse effect gases, which contribute to the environmental problem known as climate change.